RMU 2017
DOI: 10.29193/rmu.33.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome por infusión de propofol: reporte de un caso

Abstract: ResumenEl propofol es un anestésico ampliamente utilizado en las unidades de cuidados intensivos. Su empleo puede provocar un efecto adverso poco frecuente pero extremadamente grave, conocido como síndrome por infusión de propofol (SIP), caracterizado por inestabilidad hemodinámica, rabdomiólisis, acidosis láctica y disfunción multiorgánica. Presentamos un caso de SIP con desenlace fatal, discutiendo su fisiopatología, clínica y consideraciones a tener en cuenta al emplear propofol. Palabras clave: SÍNDROME DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Another study by Cremer et al reported an incidence of 10 % in neurocritical adults treated with propofol, but this increased to 31 % in patients who received doses greater than 6 mg/kg/h. (4) Hemphill et al (3) , after analyzing 108 publications documenting 168 cases of SIP in the last 30 years (1988 -2018) Agudelo et al (5) described their experience with prolonged continuous infusion of moderate doses of propofol in 71 out of 222 critically ill pediatric patients (32 %). The mean propofol dose was 2,1 mg/kg/h and the mean duration was 6,7 days.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study by Cremer et al reported an incidence of 10 % in neurocritical adults treated with propofol, but this increased to 31 % in patients who received doses greater than 6 mg/kg/h. (4) Hemphill et al (3) , after analyzing 108 publications documenting 168 cases of SIP in the last 30 years (1988 -2018) Agudelo et al (5) described their experience with prolonged continuous infusion of moderate doses of propofol in 71 out of 222 critically ill pediatric patients (32 %). The mean propofol dose was 2,1 mg/kg/h and the mean duration was 6,7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors classify factors (2,4,11) as primary risk factors (mostly developed from critical illness and resulting in the production of endogenous catecholamines, glucocorticoids, and endogenous cytokines, contributing to cardiac, peripheral, and hepatic muscle dysfunction); Trigger factors (high doses of propofol (>4 mg/kg/h), prolonged periods (>48 h), and infusion of catecholamines and corticosteroids); and finally, genetic factors (acyl coenzyme A dehydrogenase efficiency, low carbohydrate intake, young age, previous defect in betaoxidation, and pre-existing mitochondrial disorders).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations